Produção escrita do gênero Comentário Argumentativo no Facebook por alunos da 1ª série do ensino médio de uma escola pública de Quixadá-CE - Araújo, Maria Geilivânia (2023)
The corpus of this study is the written production of the Argumentative Comment genre on Facebook by students in the first year of high school at a public school in Quixadá-Ce. This is a qualitative study whose method is action research. Our general objective is to investigate the written production of the Argumentative Commentary genre on Facebook by the students, the subjects of the research, about the content covered in each post, taking into account the use of the argumentative markers of the macro-proposition of the restriction and the appropriation of the basic skills for the adequacy of the genre in question, for this inverted to investigate the texts produced by the participating subjects, in order to observe their performance in the process of writing the proposed genre. We start from the basic hypothesis that our subjects' argumentative comments on Facebook can be a source of skill for textual production in the appropriation of writing strategies. Our theoretical framework is based on the studies of Bakhtin (2010 [1992]), Adam (1982, 2019), Koch and Elias (1992; 2004a; 2004b), Paveau (2021), as well as Digital Information and Communication Technologies (DICTs). The methodological process used comprises four stages: firstly, we got to know the research location, to familiarize ourselves with the school environment and the social context of the institution. Next, we read the critical fortune on the Argumentative Comment genre on Facebook, to support our analysis; then, with the research subjects, we developed five workshops on the written production of the Argumentative Comment genre on Facebook, on the themes: Fake News, Covid-19, Bullying, Sexually Transmitted Diseases (STDs) and School dropout and its effects on Brazilian society. In each workshop, we held a face-to-face class and a hybrid class with the research participants. In the face-to-face classes, we worked on the relevant and theoretical aspects of the Argumentative Comment genre on Facebook and discussed the themes mentioned above. In the hybrid classes, we used the technological tools in the school's computer lab so that the students could make argumentative comments on the topics covered in the news published in the "Master's Research" Facebook group. Finally, we analyzed the production of the Argumentative Comment genre produced by the students on each post on the Facebook social network, from a critical and analytical perspective. The research provided the subjects, students in the class under study, with ownership of writing the Argumentative Comment genre on Facebook, based on theoretical studies carried out in classroom workshops on the characteristics of the genre, as well as on the specificities and use of argumentative markers as a production strategy. In addition, during the course of the workshops, the students showed an evolution in the way they interact on social networks, as critical subjects who are aware of their responsibilities and actions when making comments on posts on the Facebook platform. In this way, we justify the importance of our research for the educational and social spheres, hoping that our study can help public school teachers to guide the production of texts on the digital platform by their students, as well as scholars who are interested in researching the subject, and can also awaken students' ability to produce argumentative texts. The success of this last request can be seen in the productions we researched. We have therefore produced a textbook to provide methodological support for teachers in the classroom.